Global Proteinuria Guidelines: Are We Nearly There Yet? - Johnson, David W (The Australian Association of Clinical Biochemists, 2011)
Assessment of albumin and/or protein excretion in the urine is a key step in the early detection and appropriate management of chronic kidney disease. The approach to testing for albuminuria/proteinuria in the community is variable and often suboptimal. It is hampered by: variation in laboratory measurement; lack of standard reference materials and testing procedures; variable definitions and units of reporting; conflicting recommendations and practices regarding who to test; and uncertainty over when and how testing is most appropriately done. This review discusses the current status of proteinuria guidelines around the world and the key clinical issues that need to be addressed before a unifying global guideline can be developed.